2023
DOI: 10.3390/molecules28072958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Inhibitory Effect and Mechanism of Euphorbia Factor L3 against Phytophthora capsici

Abstract: Phytophthora capsici is a highly destructive phytopathogenic oomycete with a broad host range and is responsible for tremendous losses. Euphorbia factor L3 (EFL3) is a natural plant-derived compound that has been widely studied in medicine and cosmetic applications. In this study, the sensitivity of 105 P. capsici isolates to EFL3 was determined, and the biological activity and physiological effects of EFL3 against P. capsici were investigated. The median effective concentration (EC50) values for EFL3 inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Meanwhile, rhein was also found to significantly damage the mycelial cell wall integrity of P. capsici , which was verified by AKP activity determination and a CFW staining assay. Similar results showing damage to the cell wall integrity have been reported in Geotrichum citri‐aurantii treated with peppermint essential oil or P. capsici treated with euphorbia factor L 3 28,29 . Moreover, the OM and TEM results indicated that the morphology and ultrastructure of mycelia were altered after treating P. capsici with rhein.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Meanwhile, rhein was also found to significantly damage the mycelial cell wall integrity of P. capsici , which was verified by AKP activity determination and a CFW staining assay. Similar results showing damage to the cell wall integrity have been reported in Geotrichum citri‐aurantii treated with peppermint essential oil or P. capsici treated with euphorbia factor L 3 28,29 . Moreover, the OM and TEM results indicated that the morphology and ultrastructure of mycelia were altered after treating P. capsici with rhein.…”
Section: Discussionsupporting
confidence: 82%
“…Several plant extracts exert antifungal functions by acting directly or indirectly on the cell membrane and cell wall of fungi, destroying the permeability of the cell membrane, damaging the integrity of the cell wall, and leaking important cell components 27,29 . Given the satisfactory antifungal activity of rhein against P. capsici , the antifungal mechanism of rhein was further investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation